2005
DOI: 10.3928/01913913-20050101-03
|View full text |Cite
|
Sign up to set email alerts
|

Cataract and Ocular Hypertension in Children on Inhaled Corticosteroid Therapy

Abstract: Purpose: To ascertain the incidence of posterior subcapsular cataract and ocular hypertension in a cohort of children ⩽ 12 years on inhaled steroid therapy. Patients and Methods: In this prospective study, a detailed history regarding corticosteroid therapy was obtained for children attending an asthma clinic. The presence and type of lens changes (cataract) was recorded and intraocular pressure (IOP) was measured. The children underwent another eye exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…This could be due to the fact that the subjects were not followed for a longer period. Nevertheless, 7 (10%) of the subjects enrolled in Group 1 had been using ICS for ≥ 6 years and showed no evidence of cataract on ophthalmological evaluation, further confirming the report of previous studies 21 23 27 30 which have demonstrated the lack of association of ICS with posterior sub-capsular cataract.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This could be due to the fact that the subjects were not followed for a longer period. Nevertheless, 7 (10%) of the subjects enrolled in Group 1 had been using ICS for ≥ 6 years and showed no evidence of cataract on ophthalmological evaluation, further confirming the report of previous studies 21 23 27 30 which have demonstrated the lack of association of ICS with posterior sub-capsular cataract.…”
Section: Discussionsupporting
confidence: 86%
“… 35 The mean IOP observed in our study is similar to that reported by other studies that evaluated a pediatric study cohort. 20 21 32 Three (4%) children in our study group had an unexplained IOP reading above 20 mmHg and mean CCT values of 512, 571, and 542 μ m, respectively, which did not vary on the second measurement session after 1 week. No optic disc changes were noticed in these patients on ophthalmological evaluation.…”
Section: Discussionmentioning
confidence: 66%
“…The titles and abstracts of 8,026 studies were screened, with 7,328 studies excluded. The full texts of 698 articles were reviewed, with 35 articles [ 13 47 ] meeting all inclusion criteria. Our repeated database search generated 3077 results, with 431 duplicates removed and an additional 44 articles removed as they were duplicates from the overlapping search period from November 2012 to January 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the 46 included studies ( Table 1 ), six types of study design were noted: 24 randomized control trials (17–19, 21, 23–26, 28–30, 33, 36–43, 45–47,[ 57 ], 15 (33%) cohort studies [ 13 15 , 20 , 22 , 27 , 48 , 49 , 51 56 , 58 ], 4 pooled analyses of open-label RCT [ 31 , 32 , 35 , 44 ], 1 case-control study[ 50 ], 1 open-label trial [ 16 ] and 1 quasi-experimental study [ 33 ]. The authors of 29 studies declared pharmaceutical industry funding; 29 studies were conducted in North America and 33 studies in a clinic setting.…”
Section: Resultsmentioning
confidence: 99%
“…The administration of steroids, such as corticosteroids, used to treat inflammation either topically or systematically, has long been linked to primary open‐angle glaucoma (POAG) (Behbehani et al, ; Bernstein et al, ; Cubey, ; Garbe et al, ; Garrott and Walland, ; Kalina, ). In susceptible patients, steroids can lead to the development of ocular hypertension and POAG (Becker and Mills, ; Bernstein et al, ; Jones and Rhee, ; Kersey and Broadway, ).…”
Section: Introductionmentioning
confidence: 99%